2019
DOI: 10.1590/1984-70332019v19n1n17
|View full text |Cite
|
Sign up to set email alerts
|

Mating system analysis of Açaí-do-Amazonas (Euterpe precatoria Mart.) using molecular markers

Abstract: Euterpe precatoria (Açaí-do-Amazonas) produces fruits of which the fresh pulp is consumed. It is almost exclusively collected by extractivist farmers, because no selected genotypes are available for the establishment of plantations. For the domestication and breeding of the species, mating system studies are needed for strategy formulation. This study evaluated the mating system of a natural population of E. precatoria. Thirteen progenies were genotyped with 13 microsatellite loci by capillary electrophoresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
2
7
0
1
Order By: Relevance
“…The negative values for the fixation indices (f ) and the observed (H O ) and expected (H E ) heterozygosity coefficients indicate high genetic diversity (Nazareno and Reis, 2014), as confirmed by the excess of heterozygotes in the populations. The low f values and high H O also indicate that the result may be influenced by the reproductive system of the species (Ramos et al, 2011) which is allogamy (Ramos et al, 2018(Ramos et al, , 2019. Similar results were found in other palm species, such as Geonoma schottiana (Silva et al, 2011), Phoenix dactylifera (Arabnezhad et al, 2012) and Oenocarpus bataua (Ottewell et al, 2012), which could indicate a behavior common to plants of the family Arecaceae.…”
Section: Discussionsupporting
confidence: 67%
“…The negative values for the fixation indices (f ) and the observed (H O ) and expected (H E ) heterozygosity coefficients indicate high genetic diversity (Nazareno and Reis, 2014), as confirmed by the excess of heterozygotes in the populations. The low f values and high H O also indicate that the result may be influenced by the reproductive system of the species (Ramos et al, 2011) which is allogamy (Ramos et al, 2018(Ramos et al, , 2019. Similar results were found in other palm species, such as Geonoma schottiana (Silva et al, 2011), Phoenix dactylifera (Arabnezhad et al, 2012) and Oenocarpus bataua (Ottewell et al, 2012), which could indicate a behavior common to plants of the family Arecaceae.…”
Section: Discussionsupporting
confidence: 67%
“…The interspecific hybridization of the species E. oleracea and E. precatoria also needs to be investigated, to observe the agronomic performance and the harvest period of the hybrids, with the possibility of obtaining genotypes with an extension of the production period, depending on the genetic control of the character. On the other hand, as they are predominantly allogamous species (RAMOS et al, 2019;SANTOS et al, 2020), they can interbreed. Growing E. oleracea close to natural populations of E. precatoria, or vice versa poses the risk of contamination of native populations with the introduced species, with important consequences for the conservation of genetic resources, as there will be a change in the structure and genetic composition of native populations with natural hybridization between species.…”
Section: Resultsmentioning
confidence: 99%
“…Similarily, another leguminosae forage, Stylosanthes was described as autogamous based on morphological marker analyses (Bray and Hutton 1976). However, studies using microsatellites reported more accurate estimates (Santos-Garcia et al 2011;Sousa et al 2012;Ramos et al 2019), as the analyses are based on many loci, detect high polymorphism in any growth stage, and can be applied in many progeny samples. Thus, our results support molecular genotyping as a more precise method to evaluate mating systems.…”
Section: Discussionmentioning
confidence: 99%